Final answer:
The three points that are solutions to y = 3x^2 - 2x + 3 are (-2, 19), (1, 4), and (2, 11).
Step-by-step explanation:
- Plug in the x-coordinate of each point into the equation to find the corresponding y-coordinate.
- For point A (-2, 19), substituting -2 into the equation gives: y = 3(-2)^2 - 2(-2) + 3 = 12 + 4 + 3 = 19. So point A is a solution.
- For point B (0, 0), substituting 0 into the equation gives: y = 3(0)^2 - 2(0) + 3 = 0 - 0 + 3 = 3. So point B is not a solution.
- For point C (1, 2), substituting 1 into the equation gives: y = 3(1)^2 - 2(1) + 3 = 3 - 2 + 3 = 4. So point C is not a solution.
- For point D (1, 4), substituting 1 into the equation gives: y = 3(1)^2 - 2(1) + 3 = 3 - 2 + 3 = 4. So point D is a solution.
- For point E (2, 5), substituting 2 into the equation gives: y = 3(2)^2 - 2(2) + 3 = 12 - 4 + 3 = 11. So point E is not a solution.
- For point F (2, 11), substituting 2 into the equation gives: y = 3(2)^2 - 2(2) + 3 = 12 - 4 + 3 = 11. So point F is a solution.
Therefore, the three points that are solutions to y = 3x^2 - 2x + 3 are A (-2, 19), D (1, 4), and F (2, 11).